Exploratory testing strategies for video games:an experience report - Duarte, Yohan; Durelli, Vinicius; Nardi, Paulo Augusto; Endo, Andre Takeshi (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2023: Anais do XXII Simpósio Brasileiro de Jogos e Entretenimento Digital, 2023)
With the growth of the digital games market, the occurrence of bugs in games has a great impact and generates dissatisfaction among users. Therefore, conducting tests is necessary to avoid these events and ensure the quality of the distributed product. Among the tests that are performed in games, one that is particularly effective in identifying bugs from the user’s perspective is exploratory testing, but this is little covered in game testing literature, not providing new testers with guides or paths to be used for specific occasions. This paper reports an experience of applying exploratory testing strategies in two industrial 3D platform games. We selected seven well-known strategies of exploratory testing and conducted a study that involved the definition of a game testing procedure and proper adaptations for the games under test. By applying the game testing procedure, 75 bugs with low, medium and high severity were detected. The lessons learned and the routines carried out in this study can be used by new testers in games of the same category, in an attempt to obtain better results.